Analisis Faktor Dominan Yang Berpengaruh Pada Peningkatan Produktivitas Tenaga Kerja Industri Perhotelan Gryadi Blue Pasific - Sukamdani, Nugroho Budisatrio (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
PT. Gryadi Blue Pacific is an organization engaged in the hospitality industry that continues to grow. Efforts to achieve these objectives find the dominant factors that influence the effectiveness and efficiency of the organization. Labor is a major driver in a service process and determine its current activities of the organization. Utilization of a large workforce is indispensable to the achievement of customer satisfaction expectations of the hotel. To the organizations efforts done by identifying the factors that influence the increase in labor productivity and find the dominant factor affecting the effectiveness and efficiency of the organization that eventually able to increase work productivity. The steps that can be performed are : 1). Distributing leaflets questionnaires on labor , 2). Identify the variables that affect the increase in labor productivity and 3). Correlation regression factors that affect labor productivity Preliminary test results on 30 variables considered only contained only 25 variables that have significant value, while 5 other variables have no significant value to the data exceeds the rate of 0.05%. The end result is a dominant factor influencing the selection of variables strict enough salary, incentives, awards for outstanding, fair treatment and fair, reliable leadership, loyalty to the organization and the variable effect on labor productivity in PT GBP indicated by R square value is 0.703.Keywords : dominant factors , factor analysis , hospitality organizations